ZBTB16 gene variability influences obesity-related parameters and serum lipid levels in Czech adults - Bendlová, B; Vaňková, M; Hill, M; Vacínová, G; Lukášová, P; VejraŽková, D; Šedová, L; Šeda, O; Včelák, J (Physiological research, 2017)
The data derived from rat models and the preliminary results of human studies provide strong indices of involvement of common ZBTB16 variants in a range of cardiovascular and metabolic traits. This cross-sectional study in the Caucasian cohort of 1517 Czech adults aimed to verify the hypothesis that ZBTB16 gene variation directly affects obesity and serum lipid levels. Genotyping of nine polymorphisms of the ZBTB16 gene (rs11214863, rs593731, rs763857, rs2846027, rs681200, rs686989, rs661223, rs675044, rs567057) was performed. A multivariate bidirectional regression with the reduction of dimensionality (O2PLS model) revealed relationships between basal lipid levels and anthropometric parameters and some minor ZBTB16 alleles. In men, the predictors - age and presence of minor ZBTB16 alleles of rs686989, rs661223, rs675044, rs567057 - were associated with significantly higher body mass index, waist to hip ratio, body adiposity index, waist and abdominal circumferences, higher total cholesterol and LDL cholesterol and explained 20 % of variability of these variables. In women, the predictors - age and presence of the rs686989 minor T allele - were also associated with increased anthropometric parameters and total cholesterol and LDL cholesterol but the obtained O2PLS model explained only 7.8 % of the variability of the explained variables. Our study confirmed that the selected gene variants of the transcription factor ZBTB16 influence the obesity-related parameters and lipid levels. This effect was more pronounced in men.
Keywords: dospělí; cholesterol; Female; LDL-cholesterol; Adult; Cholesterol, LDL; ženské pohlaví; průřezové studie; Obesity; lidé; Lipid Metabolism; Promyelocytic Leukemia Zinc Finger Protein; metabolismus lipidů; Cholesterol; Genetic Variation; protein promyelocytické leukemie s motivem zinkového prstu; Cross-Sectional Studies; obezita; Male; Czech Republic; Česká republika; mužské pohlaví; genetická variace; Humans